2013
DOI: 10.1159/000351995
|View full text |Cite
|
Sign up to set email alerts
|

An Update of Laparoscopy in Cervical Cancer Staging: Is It a Useful Procedure?

Abstract: Objective: It was the aim of this study to report on the role of laparoscopic staging in a large series of locally advanced cervical cancer (LACC) patients and its impact on prognosis. Methods: Consecutive patients with LACC were considered for surgical staging: gynecological examination, cystoscopy and laparoscopy with peritoneal biopsies and peritoneal fluid cytology. Results: Between February 2000 and September 2010, a total of 167 women were evaluated. In 5 patients, laparoscopy could not be performed. One… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 66 publications
0
17
1
Order By: Relevance
“…Intra-abdominal spread was detected in only 1 patient with FIGO stage IIIA (0.9%), lower than the incidence of 5 or 6% reported by Gouy et al [35] and Vidaurreta et al [27] , respectively and the incidence of 20% observed in the series by Benedetti Panici et al [33] . Surprisingly, there was no difference in survival between patients affected by intra-abdominal spread and those without spread in the study by Benedetti Panici et al Upstaging with regards to tumor spread to adjacent organs from stage IIB and III to IVA was detected in 8 of our patients (6.7%).…”
Section: Discussioncontrasting
confidence: 51%
See 3 more Smart Citations
“…Intra-abdominal spread was detected in only 1 patient with FIGO stage IIIA (0.9%), lower than the incidence of 5 or 6% reported by Gouy et al [35] and Vidaurreta et al [27] , respectively and the incidence of 20% observed in the series by Benedetti Panici et al [33] . Surprisingly, there was no difference in survival between patients affected by intra-abdominal spread and those without spread in the study by Benedetti Panici et al Upstaging with regards to tumor spread to adjacent organs from stage IIB and III to IVA was detected in 8 of our patients (6.7%).…”
Section: Discussioncontrasting
confidence: 51%
“…However, the oncological benefits of surgical staging and consequent therapy modification remain controversial. Some retrospective and prospective studies have demonstrated a significant benefit, particularly after the removal of bulky lymph nodes and the adoption of planned CRTx [14,21,24,35,43] , whereas others have not observed a significant oncological advantage [9,33] . Indeed, the only randomized trial by Lai et al [12] failed to demonstrate a benefit in survival.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite a 15.2 % rate of surgery related complications, all patients completed the planned radiotherapy. In 2013 Benedetti Panici et al [ 4 ] reported a series of 167 consecutive patients with local advanced cervical cancer who had laparoscopic staging. Minor laparoscopy complication rate was 1 %.…”
Section: Staging and Re-stagingmentioning
confidence: 99%